Multicultural Values in Islamic Religious Education and Character Education for Equitable Learning: A PRISMA Systematic Review in the Context of Indonesian Pesantren-Based Schools - Ariffah Nargis Tasliyah; Munif; Askhabul Kirom; Mochammad Faiz Sholichin (WISE Pendidikan Indonesia, 2026)
Indonesia’s religiously diverse society requires Islamic Religious Education (IRE) to cultivate both religious commitment and respect for difference. This study examines multicultural values in the 2021 Grade 11 IRE and Character Education textbook used as the core learning resource in an Islamic boarding school-integrated vocational upper secondary school in Mojokerto, Indonesia. A directed qualitative content analysis of all 331 instructional pages across ten chapters used four core codes: tolerance, deliberative participation, equality, and justice. Tolerance is the most explicit value, especially through religious harmony and protection of human life. The text also promotes peaceful preaching, respectful disagreement, social-media ethics, gender equality and educational rights, and justice in civic governance. However, values are unevenly distributed and are more consistently assessed as individual moral commitments than as observable practices of equitable participation. The analysis identifies a textbook-task-assessment alignment gap: discussion and collaborative activities are present, but explicit assessment criteria for non-discrimination, inclusive voice, and the handling of prejudice are limited. The study contributes a value-to-pedagogy framework for curriculum refinement and teacher development that connects IRE with student dignity, social cohesion, and educational welfare.